2020
DOI: 10.3390/ijms21041373
|View full text |Cite
|
Sign up to set email alerts
|

The ER Unfolded Protein Response Effector, ATF6, Reduces Cardiac Fibrosis and Decreases Activation of Cardiac Fibroblasts

Abstract: Activating transcription factor-6 α (ATF6) is one of the three main sensors and effectors of the endoplasmic reticulum (ER) stress response and, as such, it is critical for protecting the heart and other tissues from a variety of environmental insults and disease states. In the heart, ATF6 has been shown to protect cardiac myocytes. However, its roles in other cell types in the heart are unknown. Here we show that ATF6 decreases the activation of cardiac fibroblasts in response to the cytokine, transforming gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Previous studies have demonstrated the role of ATF6α in cardiac alterations promoting cardiac hypertrophy, as its specific deletion in cardiac myocytes blunted the development of cardiac hypertrophy and impaired cardiac function in an animal model of transverse aortic constriction [ 40 ]. However, the role of ATF6α in cardiac fibrosis remains controversial, as some studies have shown that ATF6α decreases the differentiation of cardiac fibroblasts in myofibroblasts, reducing cardiac fibrosis [ 41 ]. In contrast, ATF6α was upregulated by the profibrotic mediator TGF-β in human cardiac fibroblasts, thus contributing to the development of cardiac fibrosis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the role of ATF6α in cardiac alterations promoting cardiac hypertrophy, as its specific deletion in cardiac myocytes blunted the development of cardiac hypertrophy and impaired cardiac function in an animal model of transverse aortic constriction [ 40 ]. However, the role of ATF6α in cardiac fibrosis remains controversial, as some studies have shown that ATF6α decreases the differentiation of cardiac fibroblasts in myofibroblasts, reducing cardiac fibrosis [ 41 ]. In contrast, ATF6α was upregulated by the profibrotic mediator TGF-β in human cardiac fibroblasts, thus contributing to the development of cardiac fibrosis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A pathway analysis further indicated an enrichment in the Heat shock factor 1 (HSF1)-dependent transactivation pathway in the stiff hECT, supporting the specific regulation of the protein folding machinery in stiff hECT (Figure 37B). There is growing evidence that the UPR and thus the protein folding plays a crucial role in the process of transition of CF into myofibroblasts [480,481]. In line with the hypothesis that cells in stiff hECT display a more pronounced myofibroblast phenotype then cells in flexible hECT, the two UPR genes EIF2K3 (PERK) and DDIT3 (CHOP) were found to be more than 2-fold higher in the stiff tissues (Figure 41B).…”
Section: Transcriptome Profile Of Hectsupporting
confidence: 62%
“…We were next curious to see whether other stress responses are also activated in BRCA -mut stroma, possibly due to DNA-damage-induced stress, or whether this phenomenon was specific to HSF1. To portray the stress network in PDAC, we stained for five additional stress-induced transcription factors (TFs): X-box binding protein 1 (XBP1) [58] and Activating Transcription Factor 6 (ATF6 [59]; ER-stress response); Hypoxia-inducible factor 1-α (HIF1α ; Hypoxia) [21], Nuclear factor erythroid-2-related factor 2 (NRF2; oxidative stress) [60], and Activating Transcription Factor 4 (ATF4 [61]; the integrated stress response; Figure 3A-E). While none of these additional stress-activated TFs showed significant differential activation (Figure S3A-E), a significant crosstalk between all these stress pathways was evident.…”
Section: Resultsmentioning
confidence: 99%